2003
DOI: 10.1002/cncr.10957
|View full text |Cite
|
Sign up to set email alerts
|

Should cytopathologists stop reporting follicular neoplasms on fine-needle aspiration of the thyroid?

Abstract: BACKGROUND As the consequence of the decreasing incidence of follicular thyroid carcinoma (FC), one wonders whether cytopathologists should stop reporting follicular neoplasms in fine‐needle aspiration (FNA) of the thyroid to minimize unnecessary thyroidectomies, if the follicular variant of papillary carcinoma (FVPC) has been excluded. METHODS Over a 6‐year‐period, 2667 ultrasound‐guided FNAs of the thyroid were performed at our practice. A total of 246 nodules (9.2%) were reported as follicular neoplasms, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 19 publications
3
48
0
1
Order By: Relevance
“…43,44 The prevalence of malignancy in this category reportedly ranges from 20% to 60% in the literature. 12,24,27,45,46 In the current study, 326 patients (63%) in this category underwent surgery. Among them, 105 patients (32%) had malignant tumors (most were FVPCT).…”
Section: -15mentioning
confidence: 67%
See 1 more Smart Citation
“…43,44 The prevalence of malignancy in this category reportedly ranges from 20% to 60% in the literature. 12,24,27,45,46 In the current study, 326 patients (63%) in this category underwent surgery. Among them, 105 patients (32%) had malignant tumors (most were FVPCT).…”
Section: -15mentioning
confidence: 67%
“…Because of their cytomorphologic similarities, distinguishing between hyperplastic (adenomatous) nodule and FN sometimes is difficult and has been the subject of many studies. [23][24][25][26][27][28] Cytologically, it is almost unfeasible to differentiate hyperplastic nodule from so-called macrofollicular adenoma or simple adenoma. We do not consider this a discrepancy, because it probably would not harm patients.…”
Section: -15mentioning
confidence: 99%
“…Yang et al, [4] suggested that, the most important clue in differentiating follicular neoplasm from nodular hyperplasia was the presence of abundant blood containing microfollicles in the follicular neoplasm [22]. However, macrofollicular adenomas have far lower microvessel density than microfollicular nodules because the space occupied by the large colloid lakes are devoid of blood vessels.…”
Section: Resultsmentioning
confidence: 99%
“…Although the cytopathologic assessment of thyroid FNAs has proven to be an excellent predictor of malignancy when the verdict is clearly benign or malignant, there remains a substantial subset of cases in which the FNA is inconclusive. These include FNAs with findings suspicious but not diagnostic of malignancy, or suggesting a follicular neoplasm, which does not distinguish benign from malignant tumors (3)(4)(5)(6)(7). Not only is an indeterminate FNA result uninformative in the management of suspicious thyroid nodules, but intraoperative frozen section is often unhelpful in the distinction of benign from malignant lesions as well (8 -14).…”
Section: Introductionmentioning
confidence: 99%